Pengaruh Kualitas Sistem, Informasi dan Layanan Sistem ERP Terhadap Kepuasan UMKM JABODETABEK - Jasmine Vyrza Qonita; Christina Dwi Astuti; Mulyadi Siregar (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aims to determine the quality of the system, the quality of information, and the quality of service for using the Enterprise Resource Planning (ERP) system on the statisfication of Micro, Small, and Medium Enterprise (MSME) players in the JABODETABEK area. The population in this study were MSME players who used the ERP system for their daily business activities and were in the JABODETABEK area. The sample data collection technique used purposive sampling with a research instrument in the form of a 5-point Likert scale questionnaire as a variable measurement. The number of samples selected was 145 samples. The data analysis method used is Structural Equation Modeling (SEM) analysis. The results showed that system quality, information quality, and service quality had a positive effect on ERP system user satisfaction.